PERAN GURU PENDIDIKAN AGAMA ISLAM DALAM MENINGKATKAN PRESTASI PESERTA DIDIK DI SD - Ardiansyah (UNISAN JURNAL, 2024)
This study aims to determine the role of the teacher in improving students in the school. This type of research is descriptive qualitative by using the methods: 1. Observation, 2. Interview or interview, 3. Documentation. The data obtained is reduced and then analyzed. The results of the analysis are obtained with the teacher’s role: 1. Mastering the lesson, 2. Managing teaching and learning programs, 3. Managing the class, 4. Using media, 5. Managing learning interactions, 6. Evaluating learning outcomes, 7. Follow-up From the lessons learned from 60 students, we can see that there are seven students whose grades have decreased, there are 14 students whose grades are fixed and 39 students’ grades have increased. From the research above, it can be concluded that Islamic Religious Education teachers have had a role in improving student achievement. The author’s suggestion for the SD Negeri 1 Sukarame Duais that teachers play a greater role in improving student achievement at the school.